Recurrent pacemaker lead thrombosis in a patient with gene polymorphism: a rare case treated with thrombolytic therapy - S. Selim Ayhan; Serkan Öztürk; Mehmet Fatih Özlü; Selma Düzenli (KARE Publishing, 2013)
Pacemaker (PM)-related thrombosis is an infrequent complication of pacing. We present the case of a 58-year-old man with heart failure and atrial fibrillation who had recurrent episodes of PM lead thrombosis while undergoing anticoagulation therapy. The patient was admitted to the hospital with complaints of dyspnea and palpitation. Echocardiography revealed normal right ventricular dimensions and an enlarged left ventricle with poor contractility and an ejection fraction of 20%. Transesophageal echocardiography demonstrated a large, mobile thrombus in the right atrium that was attached to the PM lead. The patient was successfully treated with a thrombolytic agent. Genetic tests revealed that the patient was a heterozygous carrier of the methylenetetrahydrofolate reductase (MTHFR) gene mutation.